A comprehensive life cycle assessment study of innovative bifacial photovoltaic applied on building. (15th April 2022) - Li, Zihao; Zhang, Wei; He, Bo; Xie, Lingzhi; Chen, Mo; Li, Jianhui; Zhao, Oufan; Wu, Xin
Abstract: Bifacial photovoltaic (BPV) module is a new type of photovoltaic module. Compared with mono-facial module, it can not only rely on the direct solar radiation on the front side, but also utilize the reflected solar radiation on the back side to generate electricity, and which can greatly improve the power generation. In this article, the BPV module was innovatively applied on building, and a demonstration building was designed and set up. The building includes the diversification of forms and reflection utilization. The BPV module improved power generation performance by 10.7%–12.7% compared with the mono-facial module. The inclined roof with building surface reflection has better power generation efficiency than the integrated form of building envelope with indoor reflection. Combined with the experimental test, simulation and enterprise investigation, a multi-index life cycle assessment (LCA) method for BPV modules applied on buildings is established, and include the economic, energy and environmental indicators. The application potential of different forms of BPV modules is analyzed and compared with mono-facial module. The energy payback time (EPBT) and greenhouse gas payback time (GPBT) of BPV solar house were 6.6 and 2.3 years, while the EPBT and GPBT of BPV inclined roof were 5.0 and 1.7 years. The economic analysis shows that BPV applied on building can compensate for all the input cost and even have more additional benefits. Compared with mono-facial module, BPV modules have higher benefits in all aspects. According to the LCA results, the optimization suggestions for the BPV demonstration building are given. Highlights: Bifacial photovoltaic (BPV) module is innovative applied on building envelope. Different building forms and reflection utilization of BPV systems are comparatively studied. A multi-index life cycle assessment (LCA) method for BPV system is established.